Resorbable conductive materials for optimally interfacing medical devices with the living - Sacchi, Marta; Sauter-Starace, Fabien; Mailley, Pascal; Texier, Isabelle (Frontiers in Bioengineering and Biotechnology, 2024)
Implantable and wearable bioelectronics systems focus growing interest in the medical field. Linking the micro-electronic (electronic conductivity) and biological (ionic conductivity) worlds, the biocompatible conductive materials at the electrode/tissue interface are key components in these systems. We herein focus more particularly on resorbable bioelectronics systems, able to safely degrade in biological environment once they have completed their purpose, namely stimulating or sensing biological activity in the tissues. Resorbable conductive materials are also explored in the fields of tissue engineering and 3D cell culture. After a short description of polymer-based substrates and scaffolds, and resorbable electrical conductors, we review how they can be combined to design resorbable conductive materials. Although these materials are still emerging, various medical and biomedical applications are already taking shape that could profoundly modify post-operative and wound healing follow-up. Future challenges and perspectives in the field are proposed.